Using a meta-ethnographic approach to explore the role of interprofessional education in inclusion health for health and care staff - Khan, Z; Park, S; Black, G (Emerald Insight, 2023)
Purpose: This article aims to present a systematic review and synthesis of evidence on the experiences, role and use of IPE in IH fields by using a meta-ethnographic approach including key concepts, reciprocal and refutational translation and lines of argument. Inclusion health (IH) practice suggests that the needs of excluded groups are more effectively addressed through collaborative working. Interprofessional education (IPE) occurs when two or more professions engage in shared practice and learning, resulting in improved collaboration and quality of care. Studies on IPE to train staff in fields relating to IH exist, but without a settled consensus on the best approaches/activities to foster inclusive practice.